Foreign Language Teaching Anxiety among Non-native Teachers of English: A Sample from Turkey - Gökhan Öztürk (Sakarya University Journal of Education)
Following a mixed-method approach, this study investigated foreign language teaching anxiety among non-native teachers of English in Turkish context. The participants included 103 instructors working at six different state universities and the data were collected through both qualitative and quantitative methods. The findings derived from the quantitative data revealed that teachers had a moderate level of teaching anxiety and they felt more anxious when they taught a skill in which they did not feel themselves competent enough. It was also found that gender and educational background did not have an effect on teaching anxiety whereas years of teaching experience significantly influenced the level of it. The results of the qualitative analysis showed that knowledge of target language items, students’ manners and knowledge of target culture were the primary factors which made the teachers feel anxious in classroom atmosphere. Finally, the study put forward several implications for in-service teacher training based on the findings.